Hypertension in type 2 diabetes: impact of glucose-lowering medications. Issue 4 (December 2016) - Krentz, Andrew J.
Abstract : Hypertension often co-exists with hyperglycaemia to elevate the risk of vascular disease. The importance of treating hypertension in type 2 diabetes is well appreciated, the benefits of good glycaemic control and effective treatment of hypertension being additive. Treating hyperglyaemia on the one hand and hypertension on the other are usually considered separate strategies of a multifactorial approach to risk reduction requiring specific antihypertensive and glucose-lowering drugs. It is well appreciated that antihypertensive medications can have effects (prodiabetic, neutral, protective against diabetes, according to drug class) on blood glucose levels. Rather less attention has been paid to the effect of glucose-lowering drugs on blood pressure (BP). Positive, neutral and negative effects on BP have been reported for different classes, with some evidence of heterogeneity between individual drugs within certain classes. In this article, the effects of glucose-lowering medication on BP are reviewed. There is a paucity of head-to-head studies of the effects of glucose-lowering medications on BP. Although BP targets in type 2 diabetes continue to be debated, there is a case for more attention to be directed towards the impact of glucose-lowering drugs on BP control.